Knowledge, Family Support and Self-Reliance Capital when Caring for Low Birth Weight Babies - Erlina Suci Astuti; Nursalam Nursalam; Shrimarti Rukmini Devy; Risa Etika (Universitas Airlangga, 2019)
Introduction: Low birth weight (LBW) infants are very susceptible to illness.LBW treatment with the principle of preventing infection is very important athome. The purpose of this study was to determine the relationship betweenmaternal knowledge and family support with the prevention of infection at home.Methods: This study used a correlation design. The samples were 160 motherswho had low birth weight infants with inclusion criteria mothers give birth tobabies weighing less than 2,500 grams with ages 0-2 months. The samples wereobtained through purposive sampling. The dependent variable was the mother'sability to prevent infection while the independent variable was the mother'sknowledge and family support. The instruments used were questionnaires. Thisresearch analyzed using Spearman Rho.Results: The results showed that there was a strong correlation betweenknowledge and the ability to prevent infection in treating low birth weight (r =0.696; p = 0.00) and that there was a moderate correlation between familysupport and infection prevention ability when treating a low birth weight (r =0.54. p = 0.000).Conclusion: Factors of maternal knowledge about infection prevention andfamily support need to be considered in increasing the ability of mothers to carefor babies with LBW. The factor of maternal knowledge about prevention ofinfection has a strong correlation value when compared to family support factors.Further research is needed on the model of increasing maternal knowledge aboutLBW infants during home care.